Childhood ganglioneuroma: experience of the Children's Cancer Hospital Egypt. Issue 2 (December 2018) - Fawzy, Mohamed; EL Zomor, Hossam; EL Kinaai Mostafa, Naglaa A.E.; Taha, Gehad; Abdelalim, Sara; Refaat, Amal; Amr, Mai; El-Shafiey, Maged
Abstract : Background: Ganglioneuroma (GN) is an uncommon benign neuroblastic tumor. They can arise de novo or from spontaneous or therapy-induced differentiation. Surgical excision is the treatment of choice with no role for chemotherapy. Ganglioneuroblastoma (GNB) is the intermediate part of the spectrum. Ganglioneuroblastoma intermixed (GNBi) is always favorable with many studies relating its behavior and management to GN. GN can be the dominant pathology of GNB on a core or an open biopsy material. Resection specimen can reveal immature neuroblasts and/or neuropil reclassifying the diagnosis to malignant GNB, whether nodular or intermixed, with further re-evaluation for risk stratification and biologic state. Aim: The aim of this study was to evaluate the clinicopathologic features and outcome of ganglioneuromatous tumor. The study also included cases that were initially diagnosed as GN on a biopsy material and was reclassified as GNB on resection or open biopsy material. The study highlights the impact of missampling on reclassification with comparison of clinicopathologic features and outcome of the latter. Patients and methods: The study included cases that were diagnosed as GN at the Children's Cancer Hospital Egypt 57357 during the period from July 2007 to July 2017. The study also included cases that were diagnosed as GN on biopsy material and was reclassified as GNB. Results: A total of 1429 patients were diagnosed as having neuroblastic tumors, of which 29 (2.02%) patients were diagnosed as GN. GN patients had an age range from 31.2 to 147.6. Men dominated over women (72.4%), extra-adrenal location being 65.5%. Six (20.7%) patients had intraspinal extension. As for surgery, 13 (86.6%) patients had complete mass resection and two (13.3%) patients had incomplete removal. Fourteen (48.3%) patients did not have surgery. GN cases that were reclassified to GNB had an age range from 19.2 to 199.2 months. Women (79.2%) were more than men (20.8%). Twenty-one (87.5%) patients had extra-adrenal location. Ten (41.6%) patients showed intraspinal extension. Fourteen (58.3%) cases had total mass resection and 10 (41.7%) had incomplete mass resection. None of the examined bone marrow cases showed infiltration by malignant cells nor had NMYC gene amplification. Follow-up for the two groups were excellent with 3-year overall survival of 100% for GN patients, 100% for GNBi cases, and 95.8% for all GNB cases. Conclusion: GN has very good outcome with or without surgical removal of the mass. GNBi also presents nearly the same clinicopathologic features, with same favorable outcome even in cases showing incomplete resection.